Transitions through the dynamics of adaptive cycles: Evolution of the Finnish agrifood system - Kuhmonen Irene; Kuhmonen Tuomas (Elsevier Ltd, 2025)
CONTEXT
The escalating sustainability problems of the current agrifood regime call for a radical, systemic transformation. Such a transformation implies a move into a new stability domain, defined by a new set of systemic attractors. These transformations can be conceptualised as regime shifts.
OBJECTIVE
In this study, we explored the history of the Finnish agrifood system in order to learn from the past transformations of the system and to inform the current attempts to steer its development in a more sustainable direction.
METHODS
We conducted a qualitative analysis on literature discussing the history of the Finnish agrifood system by utilising the concept of the adaptive cycle, which captures the cyclicity of the evolution of social-ecological systems.
RESULTS AND CONCLUSIONS
We identified six regimes from the 14th century onwards: Expansion (1334–1721), Progressive (1722–1868), Cattle (1869–1918), Premodern (1919–1944), Modernisation (1945–1994) and Globalisation (1995–). During each regime, the evolution of the system organised around specific attractors which initially opened up new possibilities for the actors, but over time, the very same attractors became the main source of vulnerability in the system. Along with the system's maturation, path-dependency created rigidity, escalating sustainability problems and decreasing room for manoeuvre for the system's actors, concomitantly decreasing the system's resilience. When an external shock related to climatic conditions, economic turbulence or wars coincided with such a rigidity, the system collapsed, the consequences of which span from food shortages to large-scale, deadly famines. The collapse of the old regime opened up the window of opportunity for a regime shift. The most profound regime shifts were related to changes in the system's metabolism and trade orientation.
SIGNIFICANCE
While the conservation phase of the adaptive cycle increases systemic vulnerabilities, it also offers an opportunity for systemic transformation. Allowing the adaptive cycle to play out on smaller scales—such as at the level of farm systems—helps to avoid collapse on the scale of the whole food system. The current agrifood regime in Finland indicates strong path-dependency and rigidity, manifesting a conservation phase, to be followed by release and reorganisation. This observation calls, first, for considering the resilience of the current system to anticipate a crisis and, second, for outlining alternative visions for the sustainable future of the agrifood system.